Rendimento e qualidade do queijo tipo Minas Frescal de cabras alimentadas com raspa de mandioca e alfalfa - Monteiro, Viviane Farina [UNESP] (2015)
In order to reduce the production cost of caprine milk, different feeding strategies have been evaluated, yet little is known about the effects of these changes in physicochemical composition of dairy products. The goal of this study was to evaluate the yield and the physicochemical parameters of the whey and the Minas Frescal type cheese produced with the milk of goats fed cassava scrapings replacing corn, and alfalfa grazing replacing the soybean meal. Eight Anglo-Nubian goats were used after lactation peak, distributed in two Latin Squares 4 x 4. The cheeses were made with individual milk of each goat to the physicochemical and yield analysis. The whey and cheeses of the treatments used did not differ in fat, protein, total solids, acidity, humidity and ashes, pH and yield levels. The milk produced by goats fed cassava scrapings and alfalfa can be used in the manufacture of Minas Frescal type cheeses without harming the whey, the yield and the physicochemical composition.